The Effect of Traditional and Cyclodextrin-Assisted Extraction Methods on Trifolium pratense L. (Red Clover) Extracts Antioxidant Potential - Kazlauskaite, Jurga Andreja; Ivanauskas, Liudas; Marksa, Mindaugas; Bernatoniene, Jurga (Antioxidants, 2022)
Red clover is the subject of numerous studies because of its antioxidant properties, the positive influence of isoflavones on the health, and its potential use in the prevention and treatment of chronic diseases. The right excipients, such as cyclodextrins, can increase the profile of valuable phenolic compounds in extraction media to obtain rich in antioxidants, extracts that can be used in nutraceuticals production. The aim of this study was to investigate and compare the total phenolic content, flavonoid content, and antioxidant activity of red clover aerial parts, aqueous and ethanolic extracts prepared using traditional and cyclodextrins-assisted methods. The antioxidant activity of the extracts was established using ABTS, DPPH, FRAP, and ABTS-post column methods. It was determined that cyclodextrins significantly increased total phenolic content (compared with control)—using β-cyclodextrin 20.29% (in aqueous samples); γ-cyclodextrin 22.26% (in ethanolic samples). All the samples prepared with excipients demonstrated a strong relationship between total phenolic content and DPPH assay. Study showed that for extraction with water, the highest amounts of phenolic compounds, flavonoids and antioxidant activity will be achieved with β-cyclodextrin, but extractions with ethanol will give the best results with γ-cyclodextrin. Therefore, cyclodextrins are a great and safe tool for obtaining rich, red clover flower extracts that are high in antioxidant activity, which can be used in the pharmaceutical industry for nutraceuticals production.